Importance and Current Research on the virus transmitting destructive white-fly - Chaubey, Rahul; C., Naveen N.; Rajagopal, R. (Indian Farming, 2015)
The NAIP Subproject Component 4 had taken the investigation of Bemisia tabaci species throughout India to resolve it’s taxonomic complexity. The results revealed that more than 91 genetic groups are present in India. The size and shape of vasiform orifice, tracheal fold, antennae, wax plate and position of sensilla on antennae of adults were found to be the salient features to distinguish these populations.